The deterministic factor of hotel selection in Phuket during COVID-19:A case study of domestic tourists - Piyanuch Limapan (Prince of Songkla University, 2023)
Thesis (M.B.A.(Hospitality and Tourism Management))--Prince of Songkla University, 2022